Fussy eating and feeding difficulties in infants and toddlers consuming a cows' milk exclusion diet. Issue 6 (September 2015) - Maslin, K.; Dean, T.; Arshad, S. H.; Venter, C.
Abstract Background Cows' milk allergy (CMA) is the most common infant food allergy in the United Kingdom, requiring a strict exclusion diet. Feeding difficulties and fussy eating are also very common problems in young children and can negatively influence feeding and dietary intake in an infant with CMA. The aim of this study was to compare the levels of fussy eating and feeding difficulties in two groups of young children: a group consuming an exclusion diet for CMA and a control group of children consuming an unrestricted diet. Method Participants were recruited from allergy and health visitor clinics on the Isle of Wight. Parents completed a number of questionnaires about their child's feeding behaviour. Results One hundred and twenty‐six participants (mean age 13 months) were recruited. Participants consuming an exclusion diet for CMA had significantly higher scores for both fussy eating and feeding difficulties (p < 0.05), although overall both groups were within the normal range. A number of symptoms were found to be positively moderately correlated with higher feeding difficulty score (p < 0.05). A higher consumption of milk/milk substitute consumed per day was positively correlated to both feeding difficulties and fussy eating (p < 0.05). Conclusion Participants consuming an exclusion diet for CMA have higher scores for feeding difficulties and fussy eating than those consuming an unrestricted diet; however, the majority of participants' scores were within the normal range and did not affect the growth.